2012
DOI: 10.3329/bjz.v39i2.10578
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of <i>Giardia</i> in the effluents of a waste water treatment plant in Dhaka

Abstract: The present study was designed for the qualitative and quantitative detection of Giardia in the Pagla Sewage Treatment Plant (PSTP) in Dhaka. The physico-chemical parameters of the sewage water were also recorded. Total 72 raw and treated samples were collected from PSTP throughout the year 2008 and these were processed with the Formol-Ether Concentration method and IMS followed by microscopy to identify Giardia in the sewage water. The protozoan parasite Giardia was abundant (2.23±1.44 × 105 cyst/l) in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Asymptomatic persons can shed the G.lamblia cysts in the environment. Thus, the diagnosis of G. lamblia infection in asymptomatic with the epidemiological factors contributing to the transmission play an important role in achieving control and transmission (14). Some reports have been documented, Rosoff (15) reported that out of the 232 randomly collected specimens, 16 were positive by microscope examination and immunoassay, 6 were negative by microscopic examination but positive by immunoassay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic persons can shed the G.lamblia cysts in the environment. Thus, the diagnosis of G. lamblia infection in asymptomatic with the epidemiological factors contributing to the transmission play an important role in achieving control and transmission (14). Some reports have been documented, Rosoff (15) reported that out of the 232 randomly collected specimens, 16 were positive by microscope examination and immunoassay, 6 were negative by microscopic examination but positive by immunoassay.…”
Section: Resultsmentioning
confidence: 99%
“…Agreement observed with the results of a study showed that from 54 specimens collected from 30 patients 18 asymptomatically infected with G. lamblia and 12 with symptoms were determined to be positive (16). Other result was conducted by (14) in which the prevalence of G. lamblia infection among asymptomatic children was 37.93% by microscopy and 76.11% by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, most of them are asymptomatic and can shed the Giardia cysts in the environment. Thus, the diagnosis of G. lamblia infection in asymptomatic infection plays an important role in achieving control and transmission (3) . Clinical manifestation ranges from asymptomatic carriage to acute and chronic gastrointestinal infections (4) .…”
Section: Introductionmentioning
confidence: 99%